A Novel Telemedicine System for Care of Statewide Hand Trauma. (March 2021) - Bracey, John W.; Tait, Mark A.; Hollenberg, Sophie B.; Wyrick, Theresa O.
Background: Telemedicine is an evolving tool to increase patients' access to subspecialty care. Since 2014, Arkansas has been utilizing telemedicine in the evaluation of patients with hand injuries. The purpose of this study is to assess the effect of this novel telemedicine system for the management of hand trauma on patient transfer.Methods: We reviewed data from the first year of the telemedicine program (2014) and compared it to data from the year prior (2013). Data collection from both years included number of hand consults and need for transfer. From the 2014 data, we also recorded the use of telemedicine, type of transfer, distance of transfer, and time to disposition.Results: During 2013 (pre-telemedicine), there were 263 hand traumas identified. In all, 191 (73%) injuries required transfer to a higher level of care, while 72 (23%) were managed locally. In the first year of the telemedicine program (2014), a total of 331 hand injuries were identified. A total of 298 (90%) resulted in telemedicine consultation with 65% (195) utilizing video encounters. After telemedicine consultation, local management was recommended for 164 injuries (55%) while transfer was recommended for 134 (45%). Using telemedicine, there was a significant decrease in the percentage of transfer for hand injuries ( P < .001).Conclusions: The telemedicine program was well utilized and provided patients throughout the state with continuous access to fellowship trained hand surgeons including regions where hand subspecialty care is not available. The program resulted in a significant decrease in the number of hospital transfers for the management of acute hand trauma.